The Historical-comparative Classification of Colombian Inga (Quechua) - Parks, Roger (Kansas Working Papers in Linguistics, 1990)
Colombian Inga is of particular interest to the Quechuanist because it is the northernmost member of the Quechuan language family spoken in modern times. In the present work the relationship of Colombian Inga to other varieties of Quechua is examined. The affiliation of Inga with the Ecuadorian group of Parker's (1969a) Quechua A branch of the Quechua diasystem is evidenced by shared innovations in the phonology and morphology. Among these are the voicing of the stops /p, t, k/ after homorganic nasals and the replacement of the possessive suffix system by a set of possessive pronouns. Additional innovations unique to Colombian Inga show it to form a distinct subgroup within the Ecuadorian group of Quechua A.